Plasma-chemical Synthesis of Composite Nanodispersed Oxides - Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Razumeyko O. P. Olga Pavlovna (2011, 2011)
Title screen